Oviposition behavior of Anastrepha obliqua (Maquart, 1835) (Diptera: Tephritidae) and preference between two mango (Mangifera indica L.) varieties - Galvão-Silva, Fábio L.; Araújo, Alexandre S.; Moreira, Beatriz S.; Oliveira, Carolina P.; Joachim-Bravo, Iara S. (Entomological Communications, 2023)
Anastrepha obliqua (Macquart, 1835) (Diptera: Tephritidae) is a species of fruit fly that occurs in the Neotropical region and is associated with 78 host plants. In Brazil, the species is one of the most economically important pests for fruit growers, especially in mango cultivation in the northeast region. Evaluating the oviposition behavior of polyphagous species such as fruit flies contributes to a better understanding of their fruit choice and infestation patterns and provides a basis for developing pest management techniques. In this study, we evaluated the changes in oviposition behavior of A. obliqua at different times of day and fruit fly ages with the highest oviposition activity. In addition, we tested whether A. obliqua exhibits any preference for Tommy Atkins and/or Palmer mango varieties. Our results showed higher oviposition activity in the morning and at the ages of 15-16 and 17-18 days. We also observed a preference among females to lay eggs on Tommy mangoes over Palmer ones.